EPO production at altitude in elite endurance athletes is not associated with the sea level hypoxic ventilatory response - Chapman, R. F.; Stray-Gundersen, J.; Levine, B. D. (Journal of Science and Medicine in Sport, 2010)
The level of circulating erythropoietin (EPO) in response to a fixed level of hypoxia shows substantial inter-individual variability, the source of which is undetermined. Arterial PO2 at altitude is regulated in part by the hypoxic ventilatory response, which also shows a wide inter-individual variability. We asked if the ventilatory response to hypoxia is related to the magnitude of EPO release at moderate altitude. Twenty-six national class US distance runners (17 M, 9 F) participated in a test of isocapnic hypoxic ventilatory response (HVR) at sea level, 2-7 days prior to departure to altitude. EPO measures were obtained at sea level and after 20 h at 2500 m. HVR for all subjects was 0.21 ± 0.16 L min-1 %SaO2-1 (range 0.01-0.61 L min-1 %SaO2-1), with no significant difference between men and women. EPO was significantly increased from pre-altitude (8.6 ± 2.6 ng ml-1, range 4.0-14.6 ng ml-1) to acute altitude (16.6 ± 4.4 ng ml-1, range 5.0-27.0 ng ml-1), an increase of 92.2 ± 70.1%. There was no significant sex difference in the EPO increase. delta EPO for all subjects was not correlated with HVR (r = -0.17). Similarly, a statistically or physiologically significant correlation was not present between delta EPO and HVR within the group of men (r = -0.22) or women (r = -0.19). The variability in the acute EPO response to moderate altitude is not explained by differences in peripheral chemoresponsiveness in elite distance runners. These results suggest that factors acting downstream from the lung influence the magnitude of the acute EPO response to altitude.